Influence of gas mixture with various mass numbers of gases on operation pressure range of plasma electron source with hollow cathode - Borisko, V.N.; Petrushenya, A.A. (Вопросы атомной науки и техники, 2002)
The influence of electric nonsymmetry in plasma electron source with hollow cathode as well as gas mixture with various mass numbers of gases on performances of the source was investigated. The operating pressure ranges for various working gases were determined. The intensive low-energy electron beams were obtained in fore-vacuum working pressure range at relatively low extraction potentials.